In vitro cytotoxicity and anticancer effects of citral nanostructured lipid carrier on MDA MBA-231 human breast cancer cells - Nordin, Noraini; Yeap, Swee Keong; Muhammad, Heshu Sulaiman Rahman; Zamberi, Nur Rizi; Abu, Nadiah; Mohamad, Nurul Elyani; Chee, Wun How; Masarudin, Mas Jaffri; Abdullah, Rasedee @ Mat; Mohammed Alitheen, Noorjahan Banu (Nature Publishing Group, 2019)
Very recently, we postulated that the incorporation of citral into nanostructured lipid carrier (NLC-Citral) improves solubility and delivery of the citral without toxic effects in vivo. Thus, the objective of this study is to evaluate anti-cancer effects of NLC-Citral in MDA MB-231 cells in vitro through the Annexin V, cell cycle, JC-1 and fluorometric assays. Additionally, this study is aimed to effects of NLC-Citral in reducing the tumor weight and size in 4T1 induced murine breast cancer model. Results showed that NLC-Citral induced apoptosis and G2/M arrest in MDA MB-231 cells. Furthermore, a prominent anti-metastatic ability of NLC-Citral was demonstrated in vitro using scratch, migration and invasion assays. A significant reduction of migrated and invaded cells was observed in the NLC-Citral treated MDA MB-231 cells. To further evaluate the apoptotic and anti-metastatic mechanism of NLC-Citral at the molecular level, microarray-based gene expression and proteomic profiling were conducted. Based on the result obtained, NLC-Citral was found to regulate several important signaling pathways related to cancer development such as apoptosis, cell cycle, and metastasis signaling pathways. Additionally, gene expression analysis was validated through the targeted RNA sequencing and real-time polymerase chain reaction. In conclusion, the NLC-Citral inhibited the proliferation of breast cancer cells in vitro, majorly through the induction of apoptosis, anti-metastasis, anti-angiogenesis potentials, and reducing the tumor weight and size without altering the therapeutic effects of citral.